Model Perhitungan Titik Gelombang Pecah (Point Breaker Wave) Disekitar Pantai - Gernowo, Rahmat (BERKALA FISIKA, 2009)
In this paper will be studied numerically the point breaker wave characteristic on shore. The model equation of the surface wave based on the equations which is governed by combining the refraction-diffraction on mild slope bottom. As mathematical analysis approximation, the finite difference methods was us for understanding the characteristic behavior of the surface wave on shore. The numerical simulation is obtained from the result of the numerical computation. There are significance changes of the height of wave, which is influenced by mild slope bottom factor (shoaling), diffraction and refraction. Key Word: Point Breaker Wave, finite difference, diffraction and reffraction.